The Influence Of Culture And Attitude On Students’ Lms Acceptance In Learning Mathematics At The University Of Ha’Il In Saudi Arabia - Fahad A, Alshammari Khaled (2022)
In the past few decades, information and communication technology (ICT) has grown rapidly, promoting the use of e-learning resources such as learning management system (LMS), which is now a requirement in Saudi Arabia. LMS was adopted to increase learning experience, prepare students by teaching them technology-related skills and enabling them to become competitive, and reducing time and space use in educational processes. The theoretical basis for researching variables affecting the usage of the LMS is focused on Unified Theory of Acceptance and Use of Technology (UTAUT). On the basis of these hypotheses, it is assumed that the model constructs will improve the behavioural intention of the students to use LMS at an incremental level in studying mathematics. Only three cultural dimensions showed no significant effect on LMS usage by the students, which may be attributed to the complexities of Saudi Arabian society.